Socio-economic characteristics associated with premature mortality across small-areas in Cyprus - Lamnisos, Demetris; Middleton, Nicos (My University, 2018)
Background: Geographical investigations are a core function of public health monitoring providing the foundation for resource allocation and policies for reducing health inequalities. This study investigated the patterning in all-cause premature mortality and its association with a range of socioeconomic indicators. Methods: Standardized mortality ratios of premature adult mortality (ages 15-64) were calculated across 369 communities for the period 2009-11. The social gradient in health in terms of twenty-one 2011 census indicators was estimated in Bayesian hierarchical Poisson models with spatially unstructured and structured random effects.
Keywords: Patterning; Premature mortality; Socioeconomic indicators